Xenotransplantation and risk : regulating a developing biotechnology - Fovargue, Sara, 1971- (Cambridge : Cambridge University Press, 2012)
'Some developing biotechnologies challenge accepted legal and ethical norms because of the risks they pose. Xenotransplantation (cross-species transplantation) may prolong life but may also harm the xeno-recipient and the public due to its potential to transmit infectious diseases. These trans-boundary diseases emphasise the global nature of advances in health care and highlight the difficulties of identifying, monitoring and regulating such risks and thereby protecting individual and public health. Xenotransplantation raises questions about how uncertainty and risk are understood and accepted, and exposes tensions between private benefit and public health. Where public health is at risk, a precautionary approach informed by the harm principle supports prioritising the latter, but the issues raised by genetically engineered solid organ xenotransplants have not, as yet, been sufficiently discussed. This must occur prior to their clinical introduction because of the necessary changes to accepted norms which are needed to appropriately safeguard individual and public health'--
Introducing the issues -- Dealing with risk -- Regulating experimental procedures and medical research -- Regulatory responses to developing biotechnologies -- Challenges to legal and ethical norms : first party consent and third parties at risk -- Surveillance and monitoring : balancing public health and individual freedom -- Summary and concluding thoughts : looking to the future.
Includes bibliographical references and index.
Keywords: Xenografts; Transplantation immunology; Xenografts -- Moral and ethical aspects; Transplantation of organs, tissues, etc; Transplantation, Heterologous; Transplantation, Heterologous -- ethics; Transplantation, Heterologous -- legislation & jurisprudence